The use of indigenous plant material by local authorities in amenity horticulture in the Cape Province of South Africa - Kruger, Peter (Department of Environmental and Geographical Science, 2026)
The purpose of this study is to investigate the current use of indigenous plant material in Amenity Horticulture by local authorities in the Cape Province. It focuses on the built-up and street environments, and includes public gardens, pavements, road verges, recreational grounds, walkways and car parks which fall under the jurisdiction of local authorities. The study relates to the assertions by Bernatzky ( 1978), Poynton (1983), Dixon (1985), and Fairall (1970) that . there is a heightened interest in the use of indigenous plant species in a number of countries. It investigates what Flint (1980) calls the growing awareness amongst contemporary landscape planners towards the use of indigenous plants in landscape design. He says that the movement toward landscaping with native plants has now spread widely' but has not as yet reached its full potential. lts ultimate expression may be found in recreating natural associations of plants.